PELATIHAN PEMBELAJARAN KALAM DI ERA NEW NORMAL MELALUI MEDIA DARING ASINKRON UNTUK GURU BAHASA ARAB MADRASAH TSANAWIYAH - Kholisin; Irhamni; Moch. Wahib Dariyadi; Moh. Fauzan (Universitas Negeri Malang, 2022)
The existence of the covid 19 pandemic has forced all sectors of life to innovate, including especially the education and learning sector. Learning activities that have been carried out face-to-face, must be changed to online. This requires teachers to innovate and adapt, one of which is by mastering online learning models. This service activity is carried out to equip MTs teachers with the ability to compose and use foreign synchronous online media in learning language skills. The general purpose of this activity is to provide training to improve the ability of teachers to teach kalam based on online media. The methods used include lectures, discussions, FGDs, question and answer, problem solving and practice. At the end of the training, mentoring and evaluation were carried out. In general, before the pandemic period, as many as 61% of teachers were very rare, some even never used online media in learning. After the pandemic, as many as 42% of teachers still rarely use online media in learning. The reason in addition to network problems is due to lack of mastery. This activity was acknowledged by more than 84% of participants to be very useful, especially to improve the ability to teach Arabic based on online media. More than 61% of participants felt very confident about using online media after this training. The rest are pretty sure. They hope that this kind of training is carried out on a regular basis, with materials and topics that suit the needs of the teachers.